The intervention of the physiotherapist in the patient with dementia in palliative care - Escarigo, Fábia (2018)
Introduction: Currently there are a large number of people diagnosed with dementia. In the field of palliative care, rehabilitation interventions are often lessened. Thus, it is important to study non-pharmacological measures to improve the functional status and quality of life of these patients. Issue: What´s the intervention of the physiotherapist in the patient with dementia in palliative care? Objectives: In this systematic review of the literature we intend to identify which interventions the physiotherapists used on patient with dementia in palliative care and the benefits of these techniques. Methods: Study design - Systematic Literature Review We've inclued 12 studies with a time interval 2003-2015, in which they are addressed techniques that can be used by physiotherapists in the treatment or relief of suffering and improving quality of life of patients. Scientific papers were found in several online databases and full text such as: Online Knowledge Library, B-On, Pubmed and PEdro. Results: In this systematic review of the literature found several non-pharmacological techniques that contribute to improving the quality of life of patients with dementia. These techniques are exercise aerobic, maintenance of muscle strength, equilibrium training, touch, cognitive training, behavioral interventions, cognitive stimulation, transcutaneous electrical stimulation, exercise, music therapy, reminiscence , training activities of daily living, massage, recreation therapy, snoezelen room, multisensory stimulation, support and psychotherapy, and muscle relaxation. Conclusions: Within the multidisciplinary programs analyzed in this review the physiotherapist makes perfect sense, being the professional that uses the greatest number of non-pharmacological techniques covered. These programs can be very beneficial for decreased cognition occurring more slowly and consequently allows the maintenance of the physical and increasing the patients quality of life and their caregivers. Exercise is the most studied technique with positive results on quality of life. We found that there is little evidence of physical therapist intervention in the terminal phase of the patient with dementia. Keywords: Dementia; Alzheimer's; Physical therapy; Physiotherapist; Palliative care.